Growth behavior of tin whisker on SnAg microbump under compressive stress. (1st April 2018) - Sun, Menglong; Dong, Mengya; Wang, Dongfan; Ling, Huiqin; Hu, An-min; Li, Ming
Abstract: Tin whiskers with different morphologies form on SnAg microbumps under long-term compressive stress. High resolution transmission electron microscopy results reveal that dislocations and stacking faults can be found inside tin whiskers and the neighboring grains, and the twin boundaries are irregular regions with twinning dislocations. The dislocations can slip from the adjacent grains into the tin whisker grains through the twin boundaries, resulting in whisker growth under compressive stress. The findings are of great significance to the study of tin whisker on isolated Sn-based solders and provide insights into the reliability of 3D electronic packaging. Graphical abstract: Unlabelled Image